Candida Blood Stream Infections In Neonates - DR. MADHU SHARMA,; MD, DR. SARITA YADAV MD,; DR. APARNA MD,; DR. UMA CHAUDHARY , MD, (International Journal of Pharma and Bio Sciences, 2011)
Candida spp. are known to be the most common fungal pathogens isolated from blood cultures of neonates. The present study was undertaken to know the prevalence of candidemia in neonates and their antifungal susceptibility pattern. Candida isolates were speciated by using germ tube, carbohydrate assimilation and fermentation tests, CHROM agar and Dalmau plate culture method. Antifungal susceptibility testing to amphotericin B and fluconazole was done using E-test. A total of 56 Candida isolates were obtained over a period of one year from neonates. Of these 42 isolates were non-albicans Candida. All the isolates were sensitive to amphotericin B. Fluconazole was more commonly observed in non-albicans Candida. Candida speciation as well as antifungal susceptibility pattern need to be studied,especially in light of increasing drug resistance and newer antifungals to be evaluated for therapy.